Acoustic assessment of the fish spatio‐temporal distribution during the initial filling of the Three Gorges Reservoir, Yangtze River (China), from 2006 to 2010. (December 2013) - Wang, K.; Duan, X. B.; Liu, S. P.; Chen, D. Q.; Liu, M. D.
Summary The aim of this study was to quantify the fish fauna in the Three Gorges Dam (TGD) and assess the tendency for change as well as for any spatial and temporal distribution. Two types of echo‐sounder equipment (HTI Model 241 and Simrad EY60) were used to detect the fish density and fish spatio‐temporal distribution. Eight surveys were conducted between 2006 and 2010, with the results showing that fish abundance in the Three Gorges Reservoir (TGR) increased yearly from 15.5 to 123 ind./1000 m3, a change apparently correlated with the corresponding increase in the reservoir water level. Horizontally, fish density increased from the lower reaches to the upper reaches. Fish preferred inhabiting the area around the Zhongxian section during winter and the Chongqing section in spring. Vertically, fish density was highest in the lower layer, followed by the middle layer. The difference in fish density in different water layers observed in spring was not as evident as in the winter. Fish target strength throughout the eight investigations showed a skewed distribution with respect to fish size. The overall increasing tendency of fish density and the spatio‐temporal distribution of fish species were closely related to the water level of the TGR during the impounding period. Other influencing factors included water flow rate, water depth, reservoir shape, habitat type, and protection policy.